2022
DOI: 10.1039/d2tc00968d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the interfacial insulating shell characteristics in CaCu3Ti4O12 nanowires/polyetherimide nanocomposites for high-temperature capacitive energy storage

Abstract: A large number of studies have confirmed that encapsulating an insulating shell on the surface of high-permittivity nanofillers can effectively improve the energy storage performance of polymer-based dielectric nanocomposites. Regrettably,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Neither peak of discernable titanium oxide, calcium, nor other copper oxide compounds was detected. The lattice parameters were calculated using JADE 6.5 peak fitting and Cohen’s least mean square method, such as a = 7.387 Å, comparable to the value reported in the literature [ 8 , 30 ] and JCPDS#75-2188 for 7.391 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither peak of discernable titanium oxide, calcium, nor other copper oxide compounds was detected. The lattice parameters were calculated using JADE 6.5 peak fitting and Cohen’s least mean square method, such as a = 7.387 Å, comparable to the value reported in the literature [ 8 , 30 ] and JCPDS#75-2188 for 7.391 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Universally, polymers feature good flexibility, high electron breakdown strength, and environmental tolerance, but very low dielectric properties (less than 5), which is far below the practical application value of 50. To replenish this shortage, the filling of high- k materials can significantly improve the dielectric properties of polymers, especially the ceramic particles, including titanium dioxide (TiO 2 ), barium titanate (BT), barium strontium titanate (BST), and lead zirconate titanate (PZT) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Thus, ceramic-based polymer materials have attracted significant interest from the scientific and engineering community for their potential in charge storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Therefore, the coating of buffer layers with a low dielectric constant (such as SiO 2 $ 5, Al 2 O 3 $ 10, and ZrO 2 $ 25) onto the interface of the high-K ller is one of the most effective methods to mitigate the local electric eld distortion and suppress the free charge migration. 16,[19][20][21]29,[32][33][34][35] Our previous work results have indicated that a gradient hierarchical surface layer formed by the mediate-K of TiO 2 and Al 2 O 3 shell layers into the interface of BT NFs would potently mitigate the intensication of electric current density and local electric eld, which leads to outstanding improvement of U d and E b . [36][37][38][39][40] Based on the advantages of 1D nanollers, in the present work, large-aspect-ratio 1D hydroxyapatite nanowires (HAP NWs) as llers were prepared by a hydrothermal method, owing to their mediate-K ($150) and low dielectric loss, mechanical strength, thermal stability, and superior dielectric breakdown strength.…”
Section: Introductionmentioning
confidence: 98%
“…29–31 Therefore, the coating of buffer layers with a low dielectric constant (such as SiO 2 ∼ 5, Al 2 O 3 ∼ 10, and ZrO 2 ∼ 25) onto the interface of the high- K filler is one of the most effective methods to mitigate the local electric field distortion and suppress the free charge migration. 16,19–21,29,32–35 Our previous work results have indicated that a gradient hierarchical surface layer formed by the mediate- K of TiO 2 and Al 2 O 3 shell layers into the interface of BT NFs would potently mitigate the intensification of electric current density and local electric field, which leads to outstanding improvement of U d and E b . 36–40…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation